Isolation and Analysis of the Nisin Biosynthesis Complex NisBTC: further Insights into Their Cooperative Action - Jingqi Chen (American Society for Microbiology, 2021)
Lantibiotics are ribosomally synthesized and posttranslationally modified peptide antibiotics. Although the membrane-associated lantibiotic biosynthesis machinery has long been proposed to exist, the isolation of such a complex has not been reported yet, which limits the elucidation of the processive mechanism of lantibiotic biosynthesis.